Perancangan dan Pembuatan Mesin Penjual Makanan Otomatis Menggunakan Relai Cerdas - Purnomo, Agung, Ir. Pratomo Budi Santoso, MT, Dedi Ary Prasetya, ST (2015)
Buy is an activity that carried people or consumers to obtain the desired goods. Food is one of the examples of goods that consumers want. Food can be obtained by purchasing in stores, but it will be an obstacle if the store is closed. Technological developments into the idea of the creation of a tool that is capable of closing automatically. The tool is often called a vending machine. The purpose of this study was to design a vending machine to overcome the problems experienced by consumers and as learning materials. This tool uses PLC Zelio SR2B201BD as the main controller. Photodiode sensor used to detect coins Rp 500,00 (silver). DC motors used to propel food and LDR as detection of food issued. Food consists of three types with different prices. Food can be selected if the nominal value of the money put equal to or greater than the price of food will be selected. Users who put money one can only choose foods for Rp 500,00. Put money twice can choose food for Rp 500,00 or Rp 1000,00. Put money three times can select food for Rp 500,00, Rp 1000,00, or Rp 1500,00. Purchases can not be canceled if the money has come in and there is no change. The machine will reset and the money that has been entered can not be taken if the user does not make a selection for 30 seconds after inserting the money. The successful outcome of the tool 71 times the experiment is 68 times and 3 times failed. The percentage of successful testing of the system reached 95.77%.